2015
DOI: 10.1111/codi.12879
|View full text |Cite
|
Sign up to set email alerts
|

Pathological response of locally advanced rectal cancer to preoperative chemotherapy without pelvic irradiation

Abstract: Preoperative chemotherapy without pelvic irradiation is associated with objective pathological response and adequate local control in selected patients with LARC. Further prospective controlled studies will address the question of whether it can be used as a valuable alternative to radiochemotherapy in LARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…'Systemic therapy alone' can also induce significant response of the tumour. A case series of 22 patients with rectal cancer demonstrated an objective pathological response in 12 patients, including one patient with a complete response [68]. Prior to the start of treatment, symptomatic rectal tumours with clinical signs of obstruction should be decompressed with a colostomy to avoid treatment delays for emergency intervention.…”
Section: Rectal Cancer With Synchronous Liver Metastasesmentioning
confidence: 99%
“…'Systemic therapy alone' can also induce significant response of the tumour. A case series of 22 patients with rectal cancer demonstrated an objective pathological response in 12 patients, including one patient with a complete response [68]. Prior to the start of treatment, symptomatic rectal tumours with clinical signs of obstruction should be decompressed with a colostomy to avoid treatment delays for emergency intervention.…”
Section: Rectal Cancer With Synchronous Liver Metastasesmentioning
confidence: 99%
“…Indeed, in these settings, discussions of neoadjuvant treatment in patients contra‐indicated for CRT appear to be mainly focused on the administration of neoadjuvant chemotherapy alone . However, the role of chemotherapy as the sole modality in RC neoadjuvant treatment is not yet well established .…”
Section: Discussionmentioning
confidence: 99%
“…Recent phase II and one phase III studies evaluated the feasibility and the safety of preoperative oxaliplatinbased chemotherapy without pelvic irradiation prior to total mesorectal excision in selected patients with cT2-T3Nx rectal cancer [13][14][15]27]. These studies have shown that preoperative chemotherapy alone was associated with a high rate of complete R0 resection (100%), a low risk of postoperative local recurrence (0-2%) and progression free-survival up to 92% at 4-year in selected LARC patients.…”
Section: The Choice Of Modified Folfirinox As Preoperative Treatment For Locally Advanced Rectal Cancermentioning
confidence: 99%
“…Finally, consistent data have shown that preoperative pelvic irradiation is associated with a higher risk of long term digestive and genitourinary dysfunction compared to patients undergoing surgery alone [11,12]. A number of recent studies suggest that preoperative full-dose oxaliplatin-based chemotherapy could be efficient for local control and used as an alternative to RCT in selected LARC patients [13][14][15]. This approach could have the advantage to limit the risk of local recurrence after surgery by analogy to RCT but without the risk of late side effects associated with pelvic irradiation.…”
Section: Introductionmentioning
confidence: 99%